Stereotypical Layer of Linguistic and Cultural Consciosness: Reflex vs. Conscious Necessity - MATEVOSYAN, LIANNA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article explains the reflex nature of the stereotypical layer of linguistic and cultural consciousness, which is confirmed by the modern French linguist Zh. Dyuren’s stereolinguistic approach to the phenomena of language. It is also proved that the stereotype layer may be used by speakers as a structural basis generating different communicative meanings in the processof verbal communication.
Keywords: «linguistic and cultural» consciousness, stereotypical layer, stereotypical statements, reflex